The Measurement of Fibrinolysis in the Rat - Gallimore, M. J; Tyler, H. M; Shaw, J. T. B (Thrombosis and Haemostasis, 1971)
Methods are described for measuring fibrinolytic activity in the rat. These include dilute blood clot lysis, euglobulin clot lysis, a fibrin plate assay with euglobulin solutions, and an accelerated whole blood clot lysis technique in which limited fibrinolysis is induced with urokinase. In addition, methods have been worked out for the estimation of four plasma components closely involved in fibrinolysis: fibrinogen, factor XIII, plasma inhibitors and fibrin degradation products. The sensitivity and validity of the assays were tested by studying their capacity to detect changes resulting from the administration of eledoisin, Neohydrin and turpentine.